Prevalence of Needlestick Injuries among Healthcare Workers in Rizgary Teaching Hospital - Salah H. Ali; Peshtewan D. Majeed; Umed A. Huwiezy (Polytechnic)
Needlestick injury in healthcare settings is a global issue. Despite being recognized for many years, needlestick and sharps injuries (NSIs) continue to present a risk of occupational exposure to bloodborne pathogens for health care works (HCWs). The objectives of the study were to determine the prevalence of needlestick injuries among HCWs in Rizgary Teaching Hospital and to identify the causes of needlestick injuries. A cross-sectional study was conducted on 76 healthcare workers in Rizgary Teaching hospital; there were a total of 45 males, 31 females. The data collections were administrated using face-to-face interviews to ensure a good response rate and to ensure all questions were answered. Most (52.6%) needlestick injuries occurred in wards with syringe needles being the most common causative tool; surgery ward was the most prevalent site of needlestick injuries occurrence (42.1%). The percentage of acupuncture was high and needles were the most common cause, and most injuries occurred during the re-use of the needles. The study recommends several measures to prevent and reduce acute injuries among HCWs; these measures include health education, behavior change, safer devices, and an educational program to educate these HCWs.